Penerapan Teori Keadilan dalam Kasus Pelecehan Seksual Fisik di Indonesia: Studi Putusan Nomor 919/Pid.B/2024/Pn Plg - Prihartini Prihartini (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The application of the theory of justice in handling cases of physical sexual harassment, as regulated in Article 6 of Law Number 12 of 2022, focuses on the practical application of the theory of justice. Physical sexual harassment not only attacks the victim's physical parts but also has an indeterminate psychological impact. Appropriate sanctions in cases of sexual harassment are certainly related to the application of the theory of justice. The research problem formulation in this study is how the theory of justice is applied in judges' decisions in the law enforcement process against perpetrators of physical sexual harassment and what factors hinder the realization of justice for victims of physical sexual harassment in the Indonesian justice system. The author uses a normative research method supported by empirical data. The types and sources of data used are qualitative methods using primary, secondary, and tertiary legal materials. The author collected data through literature review and fieldwork. The literature review was obtained from laws, books, scientific papers, journals, and the internet, while the fieldwork was obtained through interviews with judges, prosecutors, advocates, and victims. The collected data will later answer the research problem formulation related to the application of the theory of justice in cases of physical sexual harassment.